Ethics curriculum in Indigenous Pacific: a Solomon Islands study. (September 2019) - Sanga, Kabini
A central feature of Indigenous Solomon Islands socialization of family, clan and tribal members is character-shaping. What this looks like, however, has not been researched. This study provides a first look at what is taught as ethics education in Indigenous Solomon Islands. Using data from a wider qualitative study of an Indigenous tribe of Mala'ita Island in the Solomon Islands archipelago, the study is authored and gifted by a Mala'ita Indigenous ethics educator to other Indigenous Pacific and other global educators and researchers. The study findings include: a clearer understanding of Indigenous Mala'ita ethics education including its integrated curriculum, its emphasis on character-shaping and its particular age-gender variations and pedagogies. The study offers pragmatic, conceptual, pedagogical, contextual and research insights for institutional and societal ethics education in Solomon Islands and other Pacific Islands modern states and to others interested in understanding ethics in context.